2007
DOI: 10.1097/ta.0b013e3181271c34
|View full text |Cite
|
Sign up to set email alerts
|

β-Blocker Exposure in Patients With Severe Traumatic Brain Injury (TBI) and Cardiac Uncoupling

Abstract: betaB exposure was associated with reduced mortality among patients with severe TBI. Though loss of HR variability has previously been associated with an increase in mortality, betaB exposure appears to be associated with increased survival across all stratifications of cardiac uncoupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 57 publications
1
51
0
Order By: Relevance
“…Although patients receiving beta-blockers had severe head injury more frequently, had lower Glasgow Coma Scale scores, and more frequently required craniotomy, beta-blocker use was an independent protective factor for mortality (odds ratio 0.54, 95% confidential interval 0.33-0.91). Other investigators have reported almost the same results [74][75][76][77]. In addition, Amory et al [72] retrospectively examined the perioperative use of beta-blockers on neurological complications in patients undergoing coronary artery bypass graft surgery and showed that the use of beta-blockers was associated with a substantial reduction in the incidence of postoperative neurological complications.…”
Section: Central Nervous System Effectsmentioning
confidence: 86%
See 2 more Smart Citations
“…Although patients receiving beta-blockers had severe head injury more frequently, had lower Glasgow Coma Scale scores, and more frequently required craniotomy, beta-blocker use was an independent protective factor for mortality (odds ratio 0.54, 95% confidential interval 0.33-0.91). Other investigators have reported almost the same results [74][75][76][77]. In addition, Amory et al [72] retrospectively examined the perioperative use of beta-blockers on neurological complications in patients undergoing coronary artery bypass graft surgery and showed that the use of beta-blockers was associated with a substantial reduction in the incidence of postoperative neurological complications.…”
Section: Central Nervous System Effectsmentioning
confidence: 86%
“…Neuroprotective effects are another possible beneficial effect of beta-blockers on the CNS [70][71][72][73][74][75][76][77]. In animal studies, Lysko et al [70] examined the neuroprotective mechanisms underlying the effects of carvedilol on cultured cerebellar neurons and on CA1 hippocampal neurons in gerbils exposed to brain ischemia.…”
Section: Central Nervous System Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of these disabilities are a direct result of secondary injury processes following the mechanical insult that lead to the development of irreversible tissue damage to the central nervous system in the hours-to-days after the primary insult [2][3][4][5]. Several studies have identified a hyperadrenergic state [6][7][8] in severe TBI patients characterized by a surge in catecholamines, inducing hypermetabolism, tachycardia, and increased cardiac and cerebral oxygen demand [9][10][11][12]. Some authors believe that the hyperadrenergic state observed in moderate to severe TBI patients is a significant contributor to increased mortality [8].…”
Section: Introductionmentioning
confidence: 98%
“…in the nuLF values) were observed in healthy controls and TBI patients The core clinical features of PSH-heart rate were correlated with, blood pressure, respiratory rate, temperature, sweating, and motor hyperactivity. Riordan et al, 2007 (46) 4,116 Reduced HRV was associated with an increase in mortality; beta B exposure appears associated with increased survival across all stratifications of cardiac uncoupling. Riordan et al, 2009 (45) 2,178 Reduced HR multiscale entropy was significantly associated with increasing mortality and is a reliable predictor of mortality in TBI patients.…”
Section: Included In the Special Issue: Consciousness And The Vegetatmentioning
confidence: 99%